Edukasi Peran Orang Tua dalam Pembentukan Karakter Anak melalui Program “Rumahku Madrasah Pertamaku” di Desa Tarowang - B. Syukroni Baso; Abdul Sakti; Kurniawan , Robi (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Community service activities with the theme "My Home is My First Madrasah" were held on September 20, 2025 in Tarowang Village, South Galesong District, Takalar Regency. This activity aims to provide education to the community, especially parents and children, regarding the importance of the role of the family as the first and primary educational institution in the formation of children's character. The activity methods used were educational lectures, discussions, and question and answer sessions which took place from 08.30 to 12.30 WITA. The results of the activity showed that participants gained a better understanding of the importance of parental role models, the habituation of religious values, effective communication within the family, and the importance of maintaining a clean home environment as part of children's character education. The enthusiasm of the participants was seen through active participation in the discussion and question and answer sessions. This activity had a positive impact in the form of increased parental awareness in implementing good parenting patterns, the formation of positive habits in the family, and increased public concern for a clean and harmonious environment. Thus, the "My Home, My First Madrasah" outreach program is expected to be the first step in developing a generation with noble character, religious character, and responsibility in family and community life.